Ответы и объяснения

Лучший Ответ!
2014-04-10T20:23:02+04:00
Cos^2(45°-a)-cos^2(60°+a)-cos75°*sin(75°-2a)=
(cos (45°-a)-cos (60°+a))*((cos (45°-a)+cos (60°+a))-cos(90-15)°*sin(90-(15+2a)= 
[-2*sin( 105/2)*sin((-15-2a)/2)]*[2*cos( 105/2)*cos((15+2a)/2)]-sin15*cos(15+2a)=
[ 2*sin( 105/2)*sin(( 15+2a)/2)]*[2*cos( 105/2)*cos((15+2a)/2)]-sin15*cos(15+2a)=
[ 2*sin( 105/2)*cos( 105/2)]*[2*sin(( 15+2a)/2)*cos((15+2a)/2)]-sin15*cos(15+2a)=
sin(2*(105/2))*sin(15+2a)-sin15*cos(15+2a)= 
sin105*sin(15+2a)-sin15*cos(15+2a)= 
sin(90+15)*sin(15+2a)-sin15*cos(15+2a)= 
cos15*sin(15+2a)-sin15*cos(15+2a)= 
sin((15+2a)-15)=sin2a